Produtividade e valor nutritivo de pastagens consorciadas com distintas leguminosas - Diehl, Michelle Schalemberg (2012)
The objective of this research was to evaluate of three grazing systems (GS) with Elephant grass (EG) + Italian ryegrass (IR) + spontaneous growing species (SGS); EG + IR + SGS + Forage peanut (FP); and EG + IR + SGS + Red clover (RC), in order to use the area in rotational grazing during all agricultural year. EG was planted in rows with a distance of 4 m each one of them. In the cool-season, IR was sowed between rows of EG; RC was sowed and the FP who has found established since 2006 was preserved on respectively GS. Experimental design was completely randomized with three treatments (GS), two replicates (paddocks) and independent evaluations (grazing cycles). For evaluation, were used lactating Holstein cows receiving 1% of BW day-1 feed supplement concentrate. The pre and post forage mass parameters, botanical and structural composition, forage production and stocking rate were evaluated. Samples were collected by the handplucking method to analyze the organic matter, mineral matter, crude protein (CP), neutral detergent fiber (NDF), in situ organic matter digestibility (ISOMD), in situ dry matter digestibility (ISDMD) of forage. Eight grazing cycle were performed during the experimental period (357 days). The values of forage production and stocking rate were 15.03, 16.33, 17.03 t ha-1 and 3.57, 3.52 and 3.65 animal unit ha-1, respectively grazing systems. Grazing systems involving grasses and forage legumes in different cycles provide use of the area during the agricultural year in rotational grazing with dairy cattle. SGS increased significantly (P≤0.05) over in GS without forage legume. Higher value of CP, ISOMD and lower of NDF for GS mixed with forage legumes. Considering the herbage mass, stocking rate and nutritive value, the pastures mixed to forage legumes showed better performance.